Honey I Shrunk the University: Navigating Through Change in Higher Education - Stephanie Boss; Krystal Brue; Shaun Calix; Jennifer Dennis; Lance Janda; Melissa Thacker (Academic Chairpersons Conference Proceedings, 2023)
Enrollment declines continue to show no mercy for post-secondary institutions, threatening the long-term stability of higher education. The Department Chairs of Business, Psychology, Social Sciences and Sports & Exercise Science, and their dean, share their planned initiatives and academic strategies that have proven helpful in changing our operation mindset while addressing some of the complex issues facing the shrinking of higher education.
Keywords: enrollment trends; concurrent; micro-credentials; work force; and leadership strategies